Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Pada Pelajaran Ekonomi Kelas XII MAN 1 Medan - Azizah, Esyha Nur; Tambunan, Khairuddin E. (SJEE (Scientific Journals of Economic Education), 2026)
This study aims to determine the effect of the application of the Discovery Learning learning model on student learning outcomes in the Economics subject of class XII MAN 1 Medan. This study uses a quantitative approach with a quasi-experimental method and a Non-equivalent Pre-test - Post-test Control Group Design. The study population was 131 students of class XII IPS MAN 1 Medan in the 2025/2026 academic year. The study sample consisted of 60 students determined through purposive sampling techniques, with 30 students as the experimental class (XII SOS B1) and 30 students as the control class (XII SOS B2). The research instrument was a learning outcome test in the form of a pre-test and post-test. Data were analyzed using the Independent Samples t-test. The results of the analysis showed a t-value of 10.647 with a significance value of Sig. (2-tailed) = 0.000